Breaking barriers: Unearthing the hindrances to embracing energy economics principles in Nigerian building projects - Ayodeji Emmanuel Oke; John Aliu; Taiwo Marcus Akinpelu; Oluwadamilare Olamide Ilesanmi; Kehinde Temitope Alade (Energy and Built Environment)
The implementation of energy economics principles (EEPs) in sustainable construction and environmental mitigation is widely acknowledged. However, limited research has focused on the hindrances faced in implementing these principles in the context of developing countries. To address this research gap, this study examines these hindrances from the perspective of professionals in the Nigerian construction industry. Existing hindrances were extracted from extant studies using a systematic literature review with predefined inclusion/exclusion criteria which helped formulate the questionnaire. Through the application of exploratory factor analysis, five clusters of hindrance factors were identified, encompassing financial constraints, inadequate policies and regulations, insufficient technological infrastructure, lack of awareness and education and stakeholder-related challenges. Furthermore, the multinomial regression analysis confirmed that the hindrances related to financial constraints, inadequate policies and regulations and insufficient technological infrastructure are the most significant barriers. This study advances scientific knowledge on the hindrances to the adoption of EEPs in Nigerian building projects, providing a comprehensive understanding of the challenges faced in the context of the Nigerian construction industry. Findings from the study will inform policymakers, industry professionals and other stakeholders about the key challenges that require attention and intervention, facilitating the development of targeted strategies and initiatives to overcome these barriers effectively.